Study of Vortex Generator Effect on Airfoil Aerodynamics Using the Computational Fluids Dynamics Method - Ayudia, Siti Aisyah; Arkundato, Artoto; Rohman, Lutfi (Computational And Experimental Research In Materials And Renewable Energy, 2020)
The lift force is one of the important factors in supporting the aircraft flying capabilities. The airplane has a section called the aircraft wing. In particular, the wing section of aircraft is called the airfoil. One of the efforts to increase the lift force is to make the flow of air fluid at the top of the airfoil more turbulent. Turbulent flow can attract momentum from the boundary layer, the result of this momentum transfer has energy that is more resistant to the adverse pressure gradient which can trigger the flow separation. Efforts that can be made to reduce separation flow and increase lift force are the addition of a turbulent generator on the upper surface of the airfoil, one type of turbulent generator is a vortex generator, a vortex generator can accelerate the transition from the laminar boundary layer to the turbulent boundary layer. This study was conducted with the aim of knowing the effect of the vortex generator on the aerodynamics of NACA-4412 using the computational fluid dynamics method. The main thing that will be investigated is the effect of the straight type vortex generator application on the lift coefficient, by comparing the plain airfoil and airfoil that has been applied to the vortex generator to vary the angle of attack. The variation of the angles of attack are 0º, 5º, 10º, 15º and the placement of the vortex generator is 24% of the leading edge. The results obtained that the lift coefficient changes with increasing angle of attack and the application of a vortex generator to an airfoil can increase the lift coefficient than a plain airfoil. The optimum increase in lift coefficient is at the angle of attack of 5º as much as 13%.